PENGOLAHAN KOLEKSI DEPOSIT DAERAH KALBAR PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI KALIMANTAN BARAT - Umulani, Anna Ima; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study discussed the management of west Kalimantan regional deposit collection at West Kalimantan provincial library and filing service. The aims of this research were to know the process and obstacles in the process of management of deposit collection activities. This research used the descriptive method with a qualitative approach that describes the event based on the data obtained. The data collections were done by observation, interview, and documentation. The result of the research showed that the process of deposit collection management has not fully used Standard Operating Procedure (SOP) because the officer has not fully understood in the process of classification and cataloging. The obstacle that occurred in the process of classification activities was the officer got difficult in determining the subject of the collection.Â Keywords: Management, Deposit Collection, Public Library